Global N2O Dashboard - Sapkota, Tek Bahadur (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The target of our data collection was to compile an up-to-date database of as many field measurements of nitrous oxide (N2O) emissions from published experiments comparing unfertilized treatments with treatments fertilized with nitrogen (N) as possible. We used the database developed by Stehfest and Bouwman (2006) as a starting point but extended the number of descriptive parameter and measured N2O emission data as much as possible.